"Groupwork or teamwork?": Creating the same page for improving team-based learning experience. Issue 1 (2nd January 2023) - Zhang, Minglei
Abstract : The increasing popularity of the team-based learning (TBL) approach signifies how much the student-centered learning environment contributes to the effectiveness of teaching. Given the need to establish an agreement for groups to communicate their visions for collaborative efforts within the teamwork, this activity provides a basic communicative template for group members to exchange their thoughts and ideas on what distinguishes teamwork from groupwork and what constitutes good teamwork. This activity essentially offers a playground for student groups to engage with the notion of teamwork, identify potential challenges in their team communication, and actively seek solutions to improve their TBL experience. Courses: This activity applies to foundational courses in communication (courses requiring students to work in a team setting for an extended time). Objectives: : This activity engages students in a conversational space within a group-based setting, sharing their understanding of what constitutes good teamwork. Thus, the activity is intended to: (1) encourage team members to communicate their goals and expectations, (2) increase the understanding of contribution and appreciation of teamwork, (3) improve the overall TBL experience for team members, and (4) help students understand the differences between group-based learning and TBL experiences.